1996
DOI: 10.3109/15563659609013774
|View full text |Cite
|
Sign up to set email alerts
|

Three Suicide Attempts with Moclobemide

Abstract: In case 1, plasma moclobemide was 2.8 mg/L with 1.8 mg/L clomipramide; in case 2, 18 mg/L; in case 3 60.9 mg/L and 4.6 mg/L 12 hours later. None of the patients showed serious effects during 24 hours of observation. Plasma moclobemide at 10 to 30 times therapeutic was not associated with major toxic effects. Moclobemide seems to be considerably less toxic than tricyclic antidepressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Analysis of the available SBP measurements taken prior to, during or after the severe headaches did not reveal any unusually elevated values. The type of adverse events at high moclobemide doses does not di¤er from those seen in the therapeutic dose range, and conÞrms the symptoms seen in cases of overdose with moclobemide as the sole ingestant (Hetzel 1992;Myrenfors et al 1993;Iwersen and Schmoldt 1996). The results of the IV tyramine pressor tests amongst recipients of 450 mg and 600 mg b.i.d.…”
Section: Discussionmentioning
confidence: 74%
“…Analysis of the available SBP measurements taken prior to, during or after the severe headaches did not reveal any unusually elevated values. The type of adverse events at high moclobemide doses does not di¤er from those seen in the therapeutic dose range, and conÞrms the symptoms seen in cases of overdose with moclobemide as the sole ingestant (Hetzel 1992;Myrenfors et al 1993;Iwersen and Schmoldt 1996). The results of the IV tyramine pressor tests amongst recipients of 450 mg and 600 mg b.i.d.…”
Section: Discussionmentioning
confidence: 74%
“…Moclobemide has been extensively evaluated in the treatment of a wide spectrum of depressive disorders and social phobia. Overall, moclobemide appears to be safe and devoid of major side effects, although it is considered as a mild antidepressant, better tolerated by older patients [175][176][177][178][179][180][181]. Moclobemide undergoes extensive metabolism with less than 1 % of the dose being excreted unchanged.…”
Section: Inhibition Of Maomentioning
confidence: 99%
“…Information on coingestants taken in these five cases was based * P = 0.028; ** P = 0.034; *** P < 0.01; **** P = 0.020. NS, Not significant; 1 , all four had coingested a tricyclic antidepressant; 2 , all had coingested proconvulsant drugs: dothiepin, doxepin, venlafaxine (3) and thioridazine; 3 , asystole occurred in one patient who coingested metoprolol and ventricular tachycardia occurred in another who coingested dothiepin. on the history, and was confirmed in each case by HPLC (Table 3).…”
Section: Toxicokineticsmentioning
confidence: 99%
“…Some authors have concluded that the drug does not cause major toxicity and is far safer than tricyclic antidepressants [3,4]. However, there are reports of fatalities from moclobemide alone [5,6] and in combination with clomipramine [6][7][8][9][10], citalopram [8] and paroxetine [11].…”
Section: Introductionmentioning
confidence: 99%